Wireless heart sound data acquisition using bluetooth - Sheikh Salleh, Sheikh Hussain (2007)
International Conference on Robotics, Vision, Signal Processing & Power Applications (ROVISP) is organized by School of Electrical and Electronic Engineering, Universiti Sains Malaysia.